2021
DOI: 10.1001/jamanetworkopen.2020.37120
|View full text |Cite
|
Sign up to set email alerts
|

Association of Performance Status With Survival in Patients With Advanced Non–Small Cell Lung Cancer Treated With Pembrolizumab Monotherapy

Abstract: Key Points Question Is Eastern Cooperative Oncology Group (ECOG) performance status at the beginning of therapy associated with survival outcomes in patients with advanced non–small cell lung cancer who are treated with palliative pembrolizumab monotherapy? Findings In this cohort study of 74 patients, those with ECOG performance status of at least 2 had significantly lower disease control, progression-free survival, and overall survival than those with per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 21 publications
16
53
0
Order By: Relevance
“…This result is consistent with previously published studies [10][11][12][13]. Worse performance status was associated with decreased efficacy of ICIs considering PFS and OS; this result is similar to previous observations [5,7] and consistent with clinical trials [22][23][24].…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with previously published studies [10][11][12][13]. Worse performance status was associated with decreased efficacy of ICIs considering PFS and OS; this result is similar to previous observations [5,7] and consistent with clinical trials [22][23][24].…”
Section: Discussionsupporting
confidence: 93%
“…Although conventional chemotherapy is not recommended for lung cancer patients with poor PS, modern anti-cancer treatments, including immunotherapies and targeted therapies, are relatively convenient and less toxic than chemotherapy. Although those treatments had been 23,24 After multivariate analysis, our study showed that PS remained an important prognostic factor for PFS and OS among older patients treated with EGFR-TKIs. More metastatic sites indicate a higher tumor burden and may reflect the aggressiveness and rapid growth of cancer cells, which might be associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 78%
“…In our study, no patients had a complete response and the partial response rate (PRR) in the overall population was slightly lower than in the KEYNOTE-024; we also found a significant decrease in PRR in patients with a PS ≥ 2. In other studies, the objective response rate (partial plus complete response) in PS ≥ 2 patients ranged between 17.9% and 45% [ 12 , 20 , 21 , 22 , 23 ]. In contrast with our results, most authors have not found significant differences according to PS [ 12 , 20 , 23 ], with the exception of Alessi et al [ 22 ], who detected a significantly poorer objective response rate in patients with a PS of 2 (43.1 vs. 25.6%), although this variable in our cohort with a PS ≥ 2 was notably lower.…”
Section: Discussionmentioning
confidence: 93%
“…The retrospective study carried out by Sehgal et al [ 20 ] included 74 patients with advanced NSCL treated in monotherapy with pembrolizumab. The purpose of this study was to determine the influence of PS on PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation